Travelling safe? Risks associated to Dirofilaria spp. infection in dogs in a tourist destination - Francesca Nonnis; Doriana Atzeni; Lia Cavallo; Simona Gabrielli; Marco Pombi; Serena Cavallero; Ilaria Bellini; Ettore Napoli; Giovanni De Benedetto; Luigi Venco; Claudia Tamponi; Antonio Scala; et al. (Current Research in Parasitology and Vector-Borne Diseases, 2025)
Dirofilaria immitis and Dirofilaria repens, the causative agents of canine heartworm disease and subcutaneous dirofilariosis, respectively, are the most studied filarioid species, given their veterinary and public health significance. Considering the environmental conditions and the role of Sardinia as a tourist destination, a study was conducted on 741 dogs to update the prevalence and the risk factors of these infections. For each animal, information regarding biological and management parameters was collected. All enrolled dogs were older than 12 months and had no macrocyclic lactones treatments in the previous year. Blood samples were obtained and analyzed by modified Knott’s test and ELISA rapid test (SNAP 4DX, IDEXX). An overall microfilaremia prevalence of 15.2% was observed; D. immitis was the most prevalent species (9.9%), followed by D. repens (5.5%), while Acanthocheilonema reconditum microfilariae were identified in 3.1% of the samples. Dirofilaria immitis antigens were detected in 12.2% of the dogs included in the study. Dirofilaria immitis infection risk was statistically significant, considering the absence of ectoparasite treatments (χ2 = 21.863, P < 0.001), shelter housing (χ2 = 6.512, P = 0.011) and residence areas (χ2 = 64.725, P < 0.001). Dirofilaria repens infection risk was significantly higher in male dogs (χ2 = 4.904, P = 0.027), along with small-sized dogs (χ2 = 5.450, P = 0.020). This study confirms that dirofilariosis remains endemic across Sardinia, emphasizing the need for integrated control strategies to reduce the risk of infection spreading, protecting both animal and human health.